2011
DOI: 10.4049/jimmunol.1002742
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Rapid Recall by Memory CD4 T Cells

Abstract: Memory T cells are distinguished from naive T cells by their rapid production of effector cytokines, although mechanisms for this recall response remain undefined. Here, we investigated transcriptional mechanisms for rapid IFN-γ production by antigen-specific memory CD4 T cells. In naive CD4 T cells, IFN-γ production only occurred following sustained antigen activation and was associated with high expression of the T-bet transcription factor required for Th1 differentiation, and T-bet binding to the IFN-γ prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…Several reports have previously linked different members of the canonical and noncanonical NFκB pathway with T-cell memory (12,13,47). Our results confirmed this role and show how NFκB signaling regulates the generation of memory T cells in the context of infection.…”
Section: Discussionsupporting
confidence: 88%
“…Several reports have previously linked different members of the canonical and noncanonical NFκB pathway with T-cell memory (12,13,47). Our results confirmed this role and show how NFκB signaling regulates the generation of memory T cells in the context of infection.…”
Section: Discussionsupporting
confidence: 88%
“…Studies in mouse models have shown that low level stimulation can modulate memory CD4 ϩ T cell function and survival at the recall level, and that a novel biochemical and transcriptional signature is imparted to memory CD4 ϩ T cells enabling efficacious responses (14,23,24). In this study, we present data showing that human memory CD4 ϩ T cells without any stimulation express a high level of T-bet compared with naive CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 72%
“…T-bet is the major transcription factor for the Th1-cell lineage commitment of CD4 ϩ T cells because of its transactivation of the Th1 effector cytokine IFN-␥ (13). Previous studies in a mouse model showed that IFN-␥ production by Ag-stimulated memory CD4 ϩ T cells occurred in the absence of significant nuclear T-bet expression or T-bet engagement on the IFN-␥ promoter (14). In addition to T-bet, STAT-1 and STAT-4 also have important roles in regulating the differentiation of Th1 cells in the presence of IL-12 or IFN-␥.…”
mentioning
confidence: 99%
“…Memory T cells are known to be more sensitive to antigen stimulation due to the presence of clustered T cell receptors on the cell surface and to the reduced dependence on costimulation (49)(50)(51)(52). Accordingly, the memory CD4 T cells evident in the MLN on day 0 of infection proliferated rapidly to high frequencies by day 7, whereas CD4 T cells elicited in the primary response to infection were barely detectable in the draining lymph node.…”
Section: Discussionmentioning
confidence: 99%